Pemanfaatan Teknologi Informasi Untuk Mendukung Kegiatan Pembelajaran Di SMP N 4 Karangmoncol - Sutono, Sutono; Arrifa'i, Abdul Rozak (Jurnal Pengabdian Dharma Bakti, 2020)
The development of information technology has brought changes in almost all aspects of human life. In the world of education improving the quality of teachers is something that must be done by the education unit, especially improving the skills of teachers in making information technology-based learning media. The aim is to improve the quality of learning processes and outcomes in schools. From the results of an interview with one of the teachers at SMPN 4 Karangmoncol Purbalingga, they have not maximized information technology to be used as a learning medium. They still use manual learning in class (calcical) so that one of the problems when the teacher has a meeting or need, the class becomes empty there is no teaching and learning process. Based on this, we are from community service trying to provide assistance in activities to improve the skills of teachers of SMPN 4 Karangmoncol in making information technology-based learning media. This training program can meet the needs of the community (teachers) in the scope of Karangmoncol Middle School 4 in order to improve the quality of teachers in Karangmoncol Middle School 4, especially in making information technology-based learning media. This training program is also carried out in order to succeed the government program for teachers so that they are literate in technology and apply it in the learning process which results in the effectiveness of achieving learning objectives.Â Keywords: improvement, skills, junior high school teachers and students, learning media, information technology.